Analysis Of Study Of Nursing Care With Nursing Problems Comfort In Clients (Review Of The Application Of Foot Massage Using Citronella Oil To Reduce Blood Pressure) - Daryanti Daryanti; Supadi Supadi; Mugi Hartoyo (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Hypertension, also known as high blood pressure, is a condition in which a person's blood pressure exceeds normal limits. This condition if not treated properly can lead to complications such as stroke, heart failure, kidney failure, and other diseases. One of the treatments that can minimize the symptoms felt by people with hypertension is foot massage using citronella oil to reduce blood pressure. The purpose of this research to eliminate discomfort in hypertensive patients by applying foot massage using citronella oil. Qualitative research with a case study research design conducted in May 2022 in the working area of ​​KRMT Wongsonegoro Hospital Semarang with a total sample of 3 respondents based on inclusion and exclusion criteria. The application of foot massage therapy using citronella oil was carried out for 3 consecutive days with a frequency of 1 time a day in the inpatient room. The application of foot massage using citronella oil has the effect of reducing systolic blood pressure from 160 mmHg to 136 mmHg and diastolic blood pressure from 90 mmHg to 84 mmHg. The conclusion there was a decrease in systolic and diastolic blood pressure in hypertensive patients after being given foot massage using citronella oil.